The effects of online education on students mental health during COVID-19 (Ta'limning zamonaviy transformatsiyasi, 2024)
This study seeks to understand the impact of online learning on students' mental well-being during the COVID-19 lockdowns. Studies have looked into how new technologies affect the quality of online learning and its impact on students' mental health. This is crucial for understanding how students are coping with their studies. Various international research studies have provided statistics on this topic. Research found that online learning during the pandemic led to students feeling depressed rather than experiencing positive effects.